The children's crusade [large type] : a novel - Packer, Ann, 1959- (Center Point Large Print, 2015)
"A portrait of a California family spanning several decades that examines the way a troubled marriage sets the course of family life and encourages adult children to grapple with the past even as they attempt to create successful families--and lives--of their own"--